Silent Victims: boys and girls exposed to gender-based violence - Alvaro Capano-Bosch; Natalie Massonnier (Revista de Psicología, 2021)
The article raises a current and significant issue of great concern to society, that is, violence targeted towards children within the family, more specifically, their exposure to gender-based violence among the parents. In Uruguay, despite the high numbers of violence experienced by children within their home; the issue of exposure has not been properly addressed neither scholarly nor professionally. The literature review is a first step which seeks to review the conceptualization, classification, and consequences of children exposure to gender-based violence among their parents. The most striking of consequences includes that this violence is considered a trauma event that causes severe psychological impacts in children, affecting their emotional well-being, their family relations, their mental and physical health. It would be especially important, both in the short and medium term, to progress empirical studies that allow for appropriate and efficient evidence-based interventions.